China's corporate credit reporting system: A comparison with the United States and Germany - Theresa Krause; Mo Chen; Lena Wassermann; Doris Fischer; Jens Grossklags (Regulation & Governance, 2022)
Corporate credit reporting (CCR), which aims at increasing trust in corporates, constitutes an intriguing, yet understudied set of regulatory institutions as it is both a regulatory object and subject at the same time. Differences in national CCR systems pose challenges for multinational companies and have increasingly become a subject of international conflicts on regulatory standards. In this context, the case of China deserves special attention since the country pursues both institutional divergence and convergence with international examples. Hence, the characterization of China's regulatory regime remains difficult. By comparing the institutional context of CCR in China to those in the United States and Germany, this paper sheds light on a specific aspect of China's complex regulatory regime. At the same time, it provides insights into the Chinese manifestation of CCR, which are important for the international business community.
Keywords: 330; China; corporate credit reporting; regulatory governance; social credit system; transparency